Using Additives for the Production of Castings from the Gray Cast Iron - Hrubovcakova, Martina; Vaskova, Iveta; Conev, Martin (Manufacturing Technology Journal, 2018)
The Cold-Box Amine method was developed in 1965 by Ashland. For more than 35 years, this method has been applied worldwide and has become the most important method of cold curing. The veining is characteristic defect of cast iron alloys, which accompanies the use of Cold Box-amine cores, the solution to this defect is the content of this paper. There are many factors that affect the surface of the casting and thus the formation of veining. In recent years, products have appeared on the market - additives to prevent veining. Castings using these products should have a smooth surface, no protrusions and other foundry defects. These products have their irreplaceable place on the foundry market, as it is often necessary to eliminate the castings that cannot be cleaned and therefore the veining cannot be removed on these castings. They are predominantly castings for the automotive industry, castings for the railway industry and, in the case of low-quality casting in these sectors, we can talk about gambling with human life. Therefore, it is necessary to pay attention to the occurrence of leaks on castings and to eliminate them with the use of the above-mentioned additives, but we must not forget about many other factors that support the creation of this foundry defect. The paper is devoted to the factors influencing the casting surface and, last but not least, to the used additives in foundries.
Keywords: veining; cold box; additives; grey cast iron